Friday

July 25, 2014

July 25, 2014

Posted by **Taeyeon** on Sunday, February 26, 2012 at 4:06pm.

A. -2 B. 0 C. 2 D. 4 E. not defined

- calculus -
**Steve**, Monday, February 27, 2012 at 12:33am3x^2+2xy+y2=2

6x + 2y + 2xy' + 2yy' = 0

x=1 ==> y=-1

6(1) + 2(-1) + 2(1)y' + 2(-1)y' = 0

6 - 2 + 2y' - 2y' = 0

4 = 0

(e) undefined

The graph is an ellipse. At (1,-1) there is a vertical tangent

**Related Questions**

calc - let y be the function of x defined implicitly by the equation x^2 -2xy +...

Calculus - Consider the equation: x^2 - 2xy + 4y^2 = 64 Write an expression of ...

calculus - simplify 6x^4-2xy^4 divided by 2xy

Calculus...URGENT..show steps please - Use implicit differentiation to find the ...

calculus - find the equation of the tangent line at the given value of x on the ...

calculus - The equation x^2 y+2xy^3=8defines y as a function of x,y=f(x), near x...

Algebra - Please look at the following simplification of an algebraic expression...

Algebra - Simplify (2xy^2+3)((2xy^2)^2-(2xy^2)(3)+(3)^2) This reminds me of (U+a...

Calculus - I am having trouble differentiating x^2 + 2lny = y (solving for dy/dx...

trigonometry - if sin where defined=1/5 and where defined is in quadrant I find ...